Endothelial dysfunction as a nexus for endothelial cell-cardiomyocyte miscommunication - Leucker, Thorsten M.; Jones, Steven P. (Frontiers in Physiology, 2014)
Most studies of the heart focus on cardiomyocytes (CM) at the exclusion of other cell types such as myocardial endothelial cells (EC). Such mono-cellular approaches propagate the presumption that EC provide a mere “passive lining” or supportive role. In fact, EC contribute to a dynamic network regulating vascular tone, cardiac development, and repair. Two distinct EC types, vascular EC and epicardial EC, possess important structural and signaling properties within both the healthy and diseased myocardium. In this review, we address EC-CM interactions in mature, healthy myocardium, followed by a discussion of diseases characterized by EC dysfunction. Finally, we consider strategies to reverse EC-CM “miscommunication” to improve patients’ outcomes in various cardiovascular diseases.